История создания и развития отдела механики горных пород - Скипочка, С.И. (Геотехническая механика, 2012)
Викладено історію створення, розвитку та найсуттєвіші наукові і прикладні результати, які отримано у відділі механіки гірських порід за часи його існування. Відмічено, що відділ перетерпів багато змін, змінилося декілька завідуючих відділом, але науковий напрямок залишився. Це – динамічні явища у гірничих масивах під час прогнозування зон, небезпечних по виникненню несподіваних викидів при проведенні виробок, вдосконаленню методів прогнозу стійкості гірничих виробок, проявлення гірського тиску під час ведення очисних робіт. History of creation is laid out, development and the most substantial scientific and applied results which are got in the department of mechanics of mountain breeds in times of his existence. It is marked, that a department suffered a lot of changes, a few managers changed by a department, but scientific direction remained. This are the dynamic phenomena in mountain ranges during prognostication of areas dangerous after the origin of the unexpected troop landings during conducting of making, to perfection of methods of prognosis of firmness of the mountain making, display of mountain pressure during the conduct of cleansing works.